Extensive sampling of Saccharomyces cerevisiae in Taiwan reveals ecology and evolution of predomesticated lineages - Lee, Tracy Jiaye; Liu, Yu-Ching; Liu, Wei-An; Lin, Yu-Fei; Lee, Hsin-Han; Ke, Huei-Mien; Huang, Jen-Pan; Lu, Mei-Yeh Jade; Hsieh, Chia-Lun; Chung, Kuo-Fang; Liti, Gianni; Tsai, Isheng Jason (Genome Research, 2022)
The ecology and genetic diversity of the model yeast Saccharomyces cerevisiae before human domestication remain poorly understood. Taiwan is regarded as part of this yeast's geographic birthplace, where the most divergent natural lineage was discovered. Here, we extensively sampled the broadleaf forests across this continental island to probe the ancestral species’ diversity. We found that S. cerevisiae is distributed ubiquitously at low abundance in the forests. Whole-genome sequencing of 121 isolates revealed nine distinct lineages that diverged from Asian lineages during the Pleistocene, when a transient continental shelf land bridge connected Taiwan to other major landmasses. Three lineages are endemic to Taiwan and six are widespread in Asia, making this region a focal biodiversity hotspot. Both ancient and recent admixture events were detected between the natural lineages, and a genetic ancestry component associated with isolates from fruits was detected in most admixed isolates. Collectively, Taiwanese isolates harbor genetic diversity comparable to that of the whole Asia continent, and different lineages have coexisted at a fine spatial scale even on the same tree. Patterns of variations within each lineage revealed that S. cerevisiae is highly clonal and predominantly reproduces asexually in nature. We identified different selection patterns shaping the coding sequences of natural lineages and found fewer gene family expansion and contractions that contrast with domesticated lineages. This study establishes that S. cerevisiae has rich natural diversity sheltered from human influences, making it a powerful model system in microbial ecology.
10.1101/gr.276286.121